Anisotropic 3D confinement of MCF-7 cells induces directed cell-migration and viscoelastic anisotropy of cell-membrane. (1st January 2023) - Edwin, Privita Edwina Rayappan George; Kumar, Sumeet; Roy, Srestha; Roy, Basudev; Bajpai, Saumendra Kumar
Abstract: Tumor-associated collagen signature-3 (TACS-3) is a prognostic indicator for breast cancer survival. It is characterized by highly organized, parallel bundles of collagen fibers oriented perpendicular to the tumor boundary, serving as directional, confining channels for cancer cell invasion. Here we design a TACS-3-mimetic anisotropic, confined collagen I matrix and examine the relation between anisotropy of matrix, directed cellular migration, and anisotropy of cell membrane-the first direct contact between TACS-3 and cell-using Michigan Cancer Foundation-7 (MCF-7) cells as cancer-model. Using unidirectional freezing, we generated ∼50 μ m-wide channels filled with collagen I. Optical tweezer (OT) microrheology shows that anisotropic confinement increases collagen viscoelasticity by two orders of magnitude, and the elastic modulus is significantly greater along the direction of anisotropic confinement compared to that along the orthogonal direction, thus establishing matrix anisotropy. Furthermore, MCF-7 cells embedded in anisotropic collagen I, exhibit directionality in cellular morphology and migration. Finally, using customized OT to trap polystyrene probes bound to cell-membrane (and not to ECM) of either free cells or cells under anisotropic confinement, we quantified the effect of matrix anisotropy on membrane viscoelasticity, both in-plane and out-of-plane, vis-à-vis the membrane. Both bulk and viscous modulus of cell-membrane of MCF-7 cells exhibit significant anisotropy under anisotropic confinement. Moreover, the cell membrane of MCF-7 cells under anisotropic confinement is significantly softer (both in-plane and out-of-plane moduli) despite their local environment being five times stiffer than free cells. In order to test if the coupling between anisotropy of extracellular matrix and anisotropy of cell-membrane is regulated by cell-cytoskeleton, actin cytoskeleton was depolymerized for both free and confined cells. Results show that cell membrane viscoelasticity of confined MCF-7 cells is unaffected by actin de-polymerization, in contrast to free cells. Together, these findings suggest that anisotropy of ECM induces directed migration and correlates with anisotropy of cell-membrane viscoelasticity of the MCF-7 cells in an actin-independent manner.